PENGARUH STRATEGI THINK-PAIR-SHARE DAN MOTIVASI BELAJAR TERHADAP PEMAHAMAN MEMBACA SISWA DI KELAS X SISWA SMA BINA CIPTA PALEMBANG - Suki, Amir (RIPTEKSI KEPENDIDIKAN PGRI, 2013)
AbstrakThis study deals with the influence of Think-Pair-Share (TPS) Strategy andÂ Learning Motivation toward Studentsâ Reading Comprehension at the TenthÂ Grade Students of SMA Bina Cipta of Palembang. This study appliedÂ experimental method with factorial design with 127 students as population.Â There were 60 students as the sample of this study. This was taken by usingÂ cluster random sampling. The analysis used t-test and two ways ANOVA.Â Based on the finding of the result of the score of the motivation questionnaireÂ in experimental group shows that 30% students had high motivation and 70%Â students had low motivation. The result of analysis test of two ways ANOVAÂ showed that there was no a significant interaction effect of TPS strategy andÂ motivation on reading comprehension, since the significant value was 0.270Â higher than 0.05.Kata Kunci: Think-Pair-Share (TPS), Motivasi, Pemahaman Membaca